Dietary Supplementation With Icariin Affects Estrogen Synthesis, Vitellogenesis, and Oocyte Development in the Chinese Mitten Crab, Eriocheir sinensis - Zheng, Xiaochuan; Liu, Wenbin; Liu, Jiadai; Zhang, Caiyan; Zhang, Ling; Gao, Fan; Zhang, Dingdong; Chi, Cheng (Frontiers in Marine Science, 2020)
In Eriocheir sinensis aquaculture, crabs feeding on an artificial diet without steroid hormones available in ice-fresh fish or snails show delayed ovarian maturation and late listing. Icariin (ICA), a safe plant-derived monomer compound, can effectively promote estradiol (E2) synthesis and ovarian development in mammals, but its effect in crustaceans has not been reported. We investigated the effects of ICA on estrogen synthesis, vitellogenesis, and oocyte development in Chinese mitten crabs fed with one of four diets containing 0, 50, 100, and 200 mg/kg ICA, respectively, for 8 weeks. Results showed that vitellogenin (VTG) contents, gonadosomatic indexes (GSIs), and oocyte volumes in ICA50 and ICA 100 crabs were significantly higher than those in the control. The highest upregulated expression of VTG in hepatopancreases and ovaries was detected in ICA100 crabs. Hemolymph E2 contents were also significantly increased in ICA100 crabs. Enzyme-linked immunosorbent assay (ELISA) and western blot analysis indicated that the increase in E2 concentrations was attributable to an elevation in aromatase protein levels in ovaries through the cyclic adenosine monophosphate (cAMP)/protein kinase A (PKA)/cAMP response element binding (CREB) protein pathway. These findings suggest that ICA could serve as a natural additive to resolve the problem of delayed ovarian maturation of crabs raised in ponds.